The ecclesiology of Stanley Hauerwas as a distinctly Christian theology of liberation (1970-2000) - Thomson, John Bromilow (2001)
Of all the concepts that informed what is often called the Enlightenment Project, liberation is arguably central. Nevertheless the experience of the past 200 years has raised serious questions about the character of this liberation and its pathology. In particular, the place of Christian theology in sustaining, concepts of freedom appears to have been marginalised in much post- Enlightenment thought, a challenge of particular significance to theologians and ethicists. Stanley Hauerwas represents one response to the manifestation of the Enlightenment Project in the United States, a response which, I believe, can be described as a distinctive theology of liberation chiefly from the Enlightenment legacy. This approach involves the integration of theology and ethics in the practices of a people whose identity is correlative to the particular narrative which they embody as that diachronic and synchronic, international community called Church. It also reflects an ambivalence about metaphysics and idealism and a preference for demonstrative, ecclesially mediated, truthful living. Yet the credibility of Hauerwas' ecclesiology as a genuinely Christian politics of liberation depends upon whether Hauerwas can not only identify the limitations of post-Enlightenment liberalism, but transcend them in a way that demonstrates the truthful character of the Christian narrative he believes to be embodied in this community called church. In order to determine whether Hauerwas' Project is a genuinely Christian theology of liberation from the Enlightenment legacy, we shall need to gauge the architecture of that project in chapter 1. Then, in chapter 2, we shall locate him in the wider post-Enlightenment debate, before doing the same in terms of the theological debate in chapter 3. This will bring us into conversation with his use of narrative and story as heuristic tools to resource the character of this ecclesiology in chapter 4, before our attempt, in chapter 5, to explore whether his ecclesial politics represent a distinctively Christian expression of liberty.